Primary caregivers' experience of raising children with autism: a phenomenological perspective - Swanepoel, Yolandi (Rhodes University, Faculty of Humanities, Department of Psychology, 2005)
Autism occupies an extreme position among childhood pathologies due to its severity, duration and impact on the family. In this qualitative study, four primary caregivers of autistic children were interviewed regarding their experiences of the diagnostic process, their post-diagnostic adjustment, and how helping professionals can improve their service rendering to these families. This study utilised a phenomenological approach to look at primary caregivers as the best-informed authority to explore and describe their lived realities and experiences of raising their autistic children in South Africa. The rationale for a phenomenological approach in this study is that such an interpretative inquiry enables material to be collected and analysed within the specific context of the subjective realities of primary caregivers of autistic children in South Africa. The researcher utilised semi-structured, in-depth, face-to-face interviews as method of data collection. Each participant was interviewed over the course of three separate interviews. The themes and categories that resulted from a content analysis of the material were grouped into two broad fields of experience, namely: (1) experiences surrounding the diagnostic process; and (2) the pervasive influence of autism on different areas of family life. In terms of experiences surrounding children's diagnosis, four themes were identified: (1) Being a new parent and making sense out of chaos; (2) Responsibility and blame; (3) Confusion and disillusionment during early experiences with helping professionals; and (4) Feelings about the diagnosis. The pervasive influence of autism on different areas of family life includes: (5) Strained family relationships; (6) Challenges of behaviour management and disciplining the autistic child; (7) Challenges of finding suitable resources for education and day-care; and (8) Maintaining the family unit and doing things as a family.
Keywords: Autism in children; Autistic children; Autism in children -- Diagnosis; Parents of autistic children